Positioning and recommendations on climate change and respiratory health 2021 - Villar Álvarez, Felipe; Díez Piña, J.M.; Pinedo Sierra, C.; Salgado Aranda, S.; de Miguel Diez, Javier (My University, 2021)
La Sociedad Madrileña de Neumología y Cirugía Torácica (Neumomadrid) está comprometida con la promoción de la salud respiratoria y con la prevención de las enfermedades que sean derivadas del cambio climático. Por ello elaboramos este documento para contribuir a concienciar a la sociedad general y al personal sanitario de la importancia de contribuir a luchar contra el cambio climático. Neumomadrid establece recomendaciones sobre un uso eficaz y sostenible de los inhaladores que permitan disminuir su huella de carbono, y sobre acciones que permitan a las sociedades científicas defender el medio ambiente. Finalmente, se recogen indicadores de medida que puedan servir para conocer el grado de compromiso con el cambio climático y llevar a cabo nuevas acciones de mejora.

The Society of Pneumology and Thoracic Surgery of Madrid (Neumomadrid) is committed to promoting respiratory health and preventing diseases caused by climate change. For this reason we have prepared this document to help raise the public´s awareness and healthcare personnel of the importance of contributing to the fight against climate change. Neumomadrid establishes recommendations on an efficient and sustainable use of inhalers, which allow to reduce their carbon footprint, and on activities for scientific societies to protect the environment. Finally, key performance indicators are collected to be used for determining the degree of climate change commitment and taking new actions to improve the situation.